Malpractice Causes and Disputes Resolution Choices - Widjaja, Gunawan; Ayuningtyas, Dumilah (UI Scholars Hub, 2015)
With respect to medical malpractice, even though it is widely used and spoken, formally there is no clear neither equivocal definition ever made. Even from the point of view of law and healthcare experts, the use of malpractice term in healthcare is still unclear. This thesis conducts literatures review and experts interview in order to find out and determine the definition of medical malpractice. This thesis also tries to find the criteria, kinds, causes, evidence to be used in malpractice lawsuits, and forum selection in resolving malpractice disputes in healthcare. This thesis provides input that in principle the legal relation in providing medical service shall be seen as contractual relation.